In vitro Engineering of Novel Bioactivity in the Natural Enzymes - Tiwari, Vishvanath (Frontiers in Chemistry, 2016)
Enzymes catalyze various biochemical functions with high efficiency and specificity. In-vitro design of the enzyme leads to novel bioactivity in this natural biomolecule that give answers of some vital questions like crucial residues in binding with substrate, molecular evolution, cofactor specificity etc. Enzyme engineering technology involves directed evolution, rational designing, semi-rational designing and structure-based designing using chemical modifications. Similarly, combined computational and in-vitro evolution approaches together help in artificial designing of novel bioactivity in the natural enzyme. DNA shuffling, error prone PCR and staggered extension process are used to artificially redesign active site of enzyme, which can alter its efficiency and specificity. Modifications of the enzyme can lead to the discovery of new path of molecular evolution, designing of efficient enzymes, locating active sites and crucial residues, shift in substrate and cofactor specificity. The methods and thermodynamics of in-vitro designing of the enzyme are also discussed. Similarly, engineered thermophilic and psychrophilic enzymes attain substrate specificity and activity of mesophilic enzymes that may also be beneficial for industry and therapeutics.